Perbedaan Pertumbuhan Bayi Usia 0-6 Bulan Yang Diberi Asi Eksklusif Dengan Yang Diberi Susu Formula Di Kecamatan Ngawi - Locitasari, Yandi; , dr. Shinta Riana, Sp.A, M. Kes; , dr. Devi Usdiana Rosyidah, M.Sc (2015)
Background: From Kemenkes RI data, that obtained data for exclusive breast-feeding to baby aged 0-6 months in Indonesia on 2012 was amounted to 37.55 %, that number was lower than 2010 and 2011 which amounted 61.3 % and 61.5 %. Jawa Timur was showed that only 47 % of baby had eksclusive breast-feeding. In 2014, from Dinkes Kabupaten Ngawi showed from 1104 babies who surveyed only 414 or 37.5 % of the baby had breastfed exclusively. Exclusive breast-feeding had an important role for the optimal physical growth and development, so it's needs special attention. The purpose of this study was to determine differences in the growth of baby aged 0-6 months who were breastfed exclusively and formula-fed in Kecamatan Ngawi . Methods: The study design is an observational cross-sectional analytic approach. Research subjects were 42 baby aged ≥6 months - 1 year which only had breast-fed exclusively and only had formula-fed in Kecamatan Ngawi. The recruitment of study subjects by cluster random sampling. Data collected by the provision of research data sheets and KMS (Kartu Menuju Sehat) . The data were analyzed by using Chi Square test by SPSS 16.00 for Windows . Results: Based on the research results obtained by the growth of infants who are exclusively breastfed are better enforced 18 (85.7 %) infant formula and enforced a total of 11 (52.4 %) baby, whereas growth babies who are not breastfed exclusively both enforced by 3 (14.3 %) formula and enforced by 10 (47.6 %) infants. Obtained Chi Square value, calculated for 5.459 and the value of p=0.019 which means that p < 0.05 . While the OR value obtained 5.45. Conclusions : There are differences in the growth of baby aged 0-6 months werebreast-fed exclusively and formula-fed in Kecamatan Ngawi. Baby who had formula-fed had 5 x risk of bad growth experience, who had breast-fed exclusively.